Performance analysis of over-constrained orthogonal parallel six-axis force sensor. (October 2022) - Niu, Zhi; Zhao, Yanzhi; Zhang, Hao; Zhou, Jingbo; Du, Renjie
Highlights: An over-constrained orthogonal parallel six-axis force sensor is proposed. This improves on the traditional parallel six-axis force sensor. Proposed sensor has simple mapping relations and good decoupling performance. The influence of parameters is analysed through numerical examples. Loading calibration experiments on two types of sensor prototypes were performed. Abstract: An over-constrained orthogonal parallel six-axis force sensor is an improvement over the traditional parallel six-axis force sensor and has the advantage of simple mapping relations. According to this improved configuration, performance parameters, such as decoupling characteristics, uniform-load characteristics, and range-limited characteristics, were used for performance analysis and were mathematically established. Then, the relation between the performance parameters and sensor design parameters was analysed numerically. Finally, a sensor prototype was designed and optimised into a second prototype based on the analysis of performance parameters. Results show that the vertical branch decoupling characteristic of the first and second prototypes were 19 % and 8.8 % full-scale (FS), respectively, and the range-limited characteristics of the first and second prototypes are 7.1 % in the Fz direction and 3.9 % FS, respectively. This shows that the proposed performance parameters can better analyse the performance of the over-constrained orthogonal parallel six-axis force sensor and optimise the sensor structure.